A Retrospective Cross-sectional Study to Assess Maxillary Canine Impactions Among Maharashtra State Population of India - S R Ashwinirani; Girish Suragimath; Sowbhagya Malligere Basavaraj (Wolters Kluwer Medknow Publications, 2024)
Background: Impacted maxillary canines are the second most impactions of teeth, causing functional and esthetic complications. Objectives: To study the type, position, and prevalence of maxillary canine impactions among Maharashtra state population of India, with cone-beam computed tomography (CBCT). Methods: A cross-sectional, descriptive, retrospective study was performed using 1200 CBCT images of maxillary jaw, retrieved from the archives of dental radiology records. All the CBCT images were assessed by a senior oral radiologist to evaluate the type, prevalence, and position of maxillary canine impactions based on Yamamoto classification. Statistical analysis was performed using frequency and percentage with a statistical software. Results: Of 1200 images, 62.3% were of males and 37.8% were of females. Unilateral canine impactions (68.3%), on the right side (64%) were more common than the bilateral canine impaction (31.7%). Maxillary canine impaction prevalence was 6.8%, which was higher among females (13.2%) than males (2.9%), with statistically significant differences. Type II canine impactions were the maximum in our population. Conclusions: The maxillary canine impaction prevalence in Maharashtra state population was 6.8% and statistically more among the females. Unilateral impactions on the right side and Type II impactions as per Yamamoto classification were more predominant.